Mapping the orbitofrontal cortex using temporal fluctuations in cerebral blood flow - Kalen J. Petersen; Manus J. Donahue; Daniel O. Claassen (Brain and Behavior, 2021)
Abstract Introduction The orbitofrontal cortex (OFC) is involved in diverse cognitive and behavioral processes including incentive valuation, decision‐making, and reinforcement learning. Anatomic and cytoarchitectonic studies divide the OFC along both medial‐lateral and rostral‐caudal axes. OFC regions diverge in structure and function, assessed in vivo using white matter tractography and blood oxygenation level‐dependent (BOLD) MRI, respectively. However, interpretation of T2*‐weighted BOLD is limited by susceptibility artifacts in the inferior frontal lobes, with the spatial pattern of these artifacts frequently assuming the geometry of OFC organization. Here, we utilize a novel perfusion‐weighted arterial spin labeling (ASL) functional connectivity approach, which is minimally susceptibility‐weighted, to test the hypothesis that OFC topology reflects correlated temporal hemodynamic activity. Methods In healthy participants (n = 20; age = 29.5 ± 7.3), 3D ASL scans were acquired (TR/TE = 3,900/13 ms; spatial resolution = 3.8 mm isotropic). To evaluate reproducibility, follow‐up scanning on a separate day was performed on a participant subset (n = 8). ASL‐based connectivity was modeled for gray matter OFC voxels, and k‐means clustering (k = 2–8) applied to correlation statistics. Results These approaches revealed both medial‐lateral and rostral‐caudal OFC divisions, confirming our hypothesis. Longitudinal reproducibility testing revealed 84% voxel clustering agreement between sessions for the k = 2 solution. Conclusion To our knowledge, this constitutes the first in vivo cortical parcellation based on perfusion fluctuations. Our approach confirms functional OFC subdivisions predicted from anatomy using a less susceptibility‐sensitive method than the conventional approach.